2017
DOI: 10.1111/1460-6984.12322
|View full text |Cite
|
Sign up to set email alerts
|

Early vocabulary development in children with bilateral cochlear implants

Abstract: Background: Children with unilateral cochlear implants (CIs) may have delayed vocabulary development for an extended period after implantation. Bilateral cochlear implantation is reported to be associated with improved sound localization and enhanced speech perception in noise. This study proposed that bilateral implantation might also promote early vocabulary development. Knowledge regarding vocabulary growth and composition in children with bilateral CIs and factors associated with it may lead to improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
4
25
0
3
Order By: Relevance
“…Some children with HI are reported to show age-appropriate levels of lexical knowledge, while others do not reach norms of children with NH. For example, group findings show that only one-third of the children perform similarly to their NH peers (e.g., Rinaldi et al 2013, Välimaa et al 2018. Interestingly, Tomblin et al (2005) showed that expressive skills of English-speaking children with HI were within the range expected for children with NH; however, the performance of children with HI showed a downward trend over a period of 24 months.…”
Section: Language Abilities Of Hi Childrenmentioning
confidence: 98%
“…Some children with HI are reported to show age-appropriate levels of lexical knowledge, while others do not reach norms of children with NH. For example, group findings show that only one-third of the children perform similarly to their NH peers (e.g., Rinaldi et al 2013, Välimaa et al 2018. Interestingly, Tomblin et al (2005) showed that expressive skills of English-speaking children with HI were within the range expected for children with NH; however, the performance of children with HI showed a downward trend over a period of 24 months.…”
Section: Language Abilities Of Hi Childrenmentioning
confidence: 98%
“…To date, no previous studies have compared the properties of IDS to these two groups. However, this finding is not entirely surprising when viewed in the context of research showing that infants with unilateral HL have delayed vocabulary development and poorer auditory and language outcomes in comparison to infants with bilateral HL (Fitzpatrick et al, 2019;Välimaa et al, 2018).…”
Section: Individual Differences In Hearing Configurationmentioning
confidence: 88%
“…Second, infants' auditory perception varies depending on whether their HL is bilateral or unilateral. For instance, infants with unilateral HL have delayed vocabulary development compared to infants with bilateral HL (Fitzpatrick et al, 2019;Välimaa et al, 2018), and infants with bilateral HL show better sound localisation acuity and speech perception in noise (Johnston, Durieux-Smith, Angus, O'Connor, & Fitzpatrick, 2009) and develop higher receptive and expressive vocabulary skills compared to infants with unilateral HL (Boons et al, 2012;Sarant, Harris, Bennet, & Bant, 2014). While no studies to date have investigated the effects of bilateral vs. unilateral HL configuration on IDS components, differences in IDS qualities to these infants could be expected given the factors described above as well as other experiential factors such as different intervention approaches for infants with unilateral and bilateral HL, later age of fitting for infants with unilateral HL (Fitzpatrick, Whittingham, & Durieux-Smith, 2014), and greater confusion among parents of infants with unilateral HL regarding effectiveness of intervention practices (Fitzpatrick et al, 2015).…”
Section: A Acoustic Features Of Infant-directed Speech To Infants Wimentioning
confidence: 99%
“…exhibited lower vocabulary scores than their peers with NH, suggesting that auditory deprivation in early ages had impeded language acquisition (Lund, 2015;Välimaa et al, 2018). Moreover, there is a general trend that the performance variability of the CI group for discrimination and identification of speech sounds is greater (as shown in Figures 1 and 2) than that of the NH group, showing that Mandarin-speaking children with similar severity of hearing loss before CI implantation do not perceive consonants and lexical tones in similar ways after CI implantation.…”
Section: Relationship Between Hearing Experience Verbal Skills Amentioning
confidence: 99%